Mentors, Role Models, and Observed Differences in Students' Construction Education Self-Efficacy and Motivation. Issue 3 (2nd July 2016) - Thevenin, Melissa K.; Elliott, Jonathan W.; Bigelow, Ben F.
ABSTRACT: Perceived self-efficacy, motivation, and the presence of mentors and role models can influence occupational and academic behavior, pursuits and success. These constructs were adapted to the construction-education domain in a quantitative survey administered to 587 students enrolled in construction management courses at three universities. Mentors and role models were defined as individuals who influence a respondent's academic decisions; mentors give advice and support, whereas role models provide inspiration. Students with a person of influence (i.e., mentor or role model) reported higher self-efficacy (p < .001) and motivation (p < .001) toward successful performance in, and completion of, construction education. In total, 80.6% of construction management students reported having a person who influenced their academic decisions, and family members were reported most frequently as the person of greatest influence; a higher percentage of female students reported having a person of influence compared to male students. This article provides insight regarding the influence of others on students' self-efficacy and motivation towards academic performance within the construction-education domain. Study limitations and areas of further research are discussed.